Migrant Women and Youth: The Challenge of Labour Market Integration - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2008)
The integration of migrant women and youth into the labour market depends upon institutional ramifications (in particular the immigration regime, the welfare model and the education system), on supply factors (in particular the educational attainment level and occupational skills, language competence, ethnic origin and the proximity to the ethnic cultural identity of the host country), and demand factors (in particular the composition by economic sectors, the division of work between the household, the informal and the market sector and the economic and technological development level).
Keywords: 330; Migrants; immigration policy; Gender gaps; welfare models; foreign born; citizenship; third country origin; second generation; education system; labour market integration; Arbeitsmarktintegration; Qualifikation; Junge Arbeitskräfte; Weibliche Arbeitskräfte; Sozialstaat; Bildungswesen; Migrationspolitik; Europa